Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Get quick and reliable solutions to your questions from knowledgeable professionals on our comprehensive Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To solve the given system of equations:
[tex]\[ \begin{aligned} x & = 12 - y \\ 2x + 3y & = 29 \end{aligned} \][/tex]
We start by substituting the expression for [tex]\( x \)[/tex] from the first equation into the second equation:
1. Substitute [tex]\( x = 12 - y \)[/tex] into [tex]\( 2x + 3y = 29 \)[/tex]:
[tex]\[ 2(12 - y) + 3y = 29 \][/tex]
2. Distribute the 2 inside the parentheses:
[tex]\[ 24 - 2y + 3y = 29 \][/tex]
3. Combine like terms:
[tex]\[ 24 + y = 29 \][/tex]
4. Solve for [tex]\( y \)[/tex]:
[tex]\[ y = 29 - 24 \][/tex]
[tex]\[ y = 5 \][/tex]
With [tex]\( y = 5 \)[/tex], we substitute back into the first equation to find [tex]\( x \)[/tex]:
5. Substitute [tex]\( y = 5 \)[/tex] into [tex]\( x = 12 - y \)[/tex]:
[tex]\[ x = 12 - 5 \][/tex]
[tex]\[ x = 7 \][/tex]
So, the solution to the system of equations is [tex]\( x = 7 \)[/tex] and [tex]\( y = 5 \)[/tex].
Thus, the correct answer is:
[tex]\[ \boxed{C: \ x = 7, \ y = 5} \][/tex]
[tex]\[ \begin{aligned} x & = 12 - y \\ 2x + 3y & = 29 \end{aligned} \][/tex]
We start by substituting the expression for [tex]\( x \)[/tex] from the first equation into the second equation:
1. Substitute [tex]\( x = 12 - y \)[/tex] into [tex]\( 2x + 3y = 29 \)[/tex]:
[tex]\[ 2(12 - y) + 3y = 29 \][/tex]
2. Distribute the 2 inside the parentheses:
[tex]\[ 24 - 2y + 3y = 29 \][/tex]
3. Combine like terms:
[tex]\[ 24 + y = 29 \][/tex]
4. Solve for [tex]\( y \)[/tex]:
[tex]\[ y = 29 - 24 \][/tex]
[tex]\[ y = 5 \][/tex]
With [tex]\( y = 5 \)[/tex], we substitute back into the first equation to find [tex]\( x \)[/tex]:
5. Substitute [tex]\( y = 5 \)[/tex] into [tex]\( x = 12 - y \)[/tex]:
[tex]\[ x = 12 - 5 \][/tex]
[tex]\[ x = 7 \][/tex]
So, the solution to the system of equations is [tex]\( x = 7 \)[/tex] and [tex]\( y = 5 \)[/tex].
Thus, the correct answer is:
[tex]\[ \boxed{C: \ x = 7, \ y = 5} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.